PERAN PASUKAN HANTU RIMBA PADA AGRESI MILITER BELANDA II DI GUNUNG TOAR 1948-1949 - Ega El Fischa; Kamaruddin Kamaruddin; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The Ghost Forest Rimba is an army formed on the result of the meeting of the people of Gunung Toar on Dutch Aggression II 1948-1949. The fighters fought with tactics of guerrilla warfare including the Ghost Jungle Troop who fought in the area of Gunung Toar. The fighting started from a Dutch troop patrol from Kuantan Bay to Lubuk Jambi, unbeknownst to Dutch troops, Dutch troops were attacked by guerrillas from Lubuk Jambi. Given the situation is not possible then the troops of aggression decided to return to Kuantan Bay when the troops of aggression back to Taluk Kuantan was already in the gang by guerrilla forces combined Hantu Rimba troops led Save Datuk Paduko with Halilintar forces led by Kasim Datuk Joindo. Precisely November 1949 at the Pasar Gunung with the position of guerrilla forces Hantu Rimba and Halilintar forces are on the hill, while the Dutch position is under the hill. In a very short time a guerrilla force named Joma Kopun managed to shoot a Dutch troop. The purpose of this research is to know the background of the formation of the Hantu Rimba Troops, the role of the Hantu Rimba Troops facing the Dutch Military Aggression II, to know the end of the struggle of the Hantu Rimba Troops in the face of the Dutch at Gunung Toar 1948-1949. The method used in this research is historical method. The research location is in Petapahan village, in Pisang Berebus village, in Pasar Gunung village. The research time starts from proposal seminar up to Thesis exam. Data collection techniques used are observation techniques, interview techniques, library techniques, documentation techniques. From the results of the research can be concluded that the Forest Hantu Rimba is an important role in the struggle to maintain Indonesia's independence, especially in Gunung ToarKeywords: Role, Ghost Force Rimba, Dutch Military Aggression II